Genetic diversity, genetic population structure and epidemiology of multidrug resistance Neisseria gonorrhoeae from Kenya - Henry Kiema Musee; Dennis Wamalabe Mukhebi (PLoS ONE, 2026)
Neisseria gonorrhoeae is the bacterial agent responsible for gonorrhea, a common sexually transmitted infection. The emergence of Neisseria gonorrhoeae multidrug-resistant (MDR) strains a presents a critical public health threat, especially due to its contribution to antimicrobial resistance (AMR) and treatment failure. Currently, resistance profiling of N. gonorrhoeae relies on phenotypic methods such as minimum inhibitory concentration (MIC) testing and identification of known resistance mutations. These are with limited application of genome-wide approaches to understand resistance evolution. The lack of genomic epidemiology data among Low- and Middle-Income Countries (LMICs) regions such as Kenya, hampers effective AMR tracking and designation of evidence-based, targeted treatments. This study aims to investigate the genetic diversity, population structure, and recombination dynamics of MDR N. gonorrhoeae isolates from Kenya using whole-genome SNP analysis. A total of 92 genomes (72 FASTQ reads and 20 assembled genomes) were retrieved from NCBI. De novo assembly, identification of AMR genes and variant calling were conducted, followed by Principal Component Analysis (PCA), Neighbor-Net clustering, nucleotide diversity (π), and linkage disequilibrium (LD) decay analysis to assess population structure and recombination patterns. Our results revealed a predominant genetic cluster with several divergent outlier strains, indicating moderate population differentiation. Despite the lack of strong geographic separation in the overall genomic structure, significant regional differences were observed in antimicrobial resistance gene burden. Western Kenyan regions (Kisumu and Kombewa) exhibited higher AMR gene counts despite genetic similarity to isolates from other regions, suggesting that local antibiotic selection pressures, rather than population isolation, are driving the accumulation of resistance determinants. Across the genome, nucleotide diversity was variable with distinct recombination hotspots. A rapid LD decay within the first 1000 bp suggested a high overall recombination rate. These results indicate that recombination plays a pivotal role in shaping genetic variability and AMR evolution in N. gonorrhoeae populations. The absence of strong geographic structure further implies that transmission dynamics, rather than regional isolation, drive the spread of resistance. In conclusion, genome-wide SNP analysis offers valuable insights into the genetic diversity and populations structure of MDR N. gonorrhoeae in Kenya. These findings support the integration of genomic surveillance into national strategies for antimicrobial resistance control. This study reveals how genetic analysis can guide better strategies to track and control drug-resistant gonorrhea in Kenya.